Kepatuhan Hukum PT. Atalian Global Services Permasalahan Pembayaran Kompensasi Terhadap 30 Pekerja/Buruh - Siallagan, Hans Lidona; Widagdo, Gatot S.; Tobing, Padimun Lumban (Neolectura, 2024)
Indonesia has regulated labor law, specially UU Cipta Kerja. In Government law No 35 of 2021 article (15), it is stated that employers have the obligation to pay compensation money to employees when their term of employment ends on a fixed-term contract (PKWT). The purpose of this research is to determine the implementation of providing compensation to PKWT at PT. Atalian Global Services to its employees in accordance with statutory regulations. The research method is normative-empirical legal research carried out using data collection methods through interview techniques with 30 sources and secondary data from the results of literature studies. The results of this research showed that the implementation of PKWT compensation at PT. Atalian Global Services does not follow Government regulation no. 35 of 2021 because the outsourcing company has not received payment from the main company, whereas according to the worker's perspective, the worker only hopes that the compensation will be paid immediately because this is the worker's right and obligation for the company.